A multiple case study of the existing residential interior spaces of selected housing units in Bistekville 2 in addressing children's spatial needs - Prieto, Maria Salome S.; Gallardo, Mildred M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This research assessed how low-income families managed the residential interior spaces of single story with loft housing units in Bistekville 2 in addressing the basic spatial needs of the children. The research aimed to determine the activities within the allocated spaces. A multiple case study approach and purposive sampling was used in selecting the three (3) families consisting of two parents and at least two children ages 7-16 years old. Furthermore, in-depth interviews with the parent and children, photo documentation and observations of the site were conducted. The interview responses of the parents and children pertaining to the household background and space utilization and allocation were tabulated and organized into themes. Images were described and organized per area for each family. Findings showed that the existing residential interior spaces of the housing units manifested similar issues such as limited space, low thermal comfort, lack of storage, and the need for privacy of the children. The study showed that the older children asked for more privacy in their sleeping areas and portrayed the concept of territoriality by Edward T. Hall. Moreover, existing interior spaces may further become problematic with the increasing needs of the children as they grow older. Therefore, the residential interior spaces of the housing units are not designed for long term use. Finally, the research suggests having a larger floor area to create a more efficient interior space in addressing all the needs of the users specifically the children. This can help in supporting the users' growing needs regardless of their financial condition.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Interior architecture -- Philippines -- Quezon City; Poor families -- Philippines -- Quezon City -- Housing; Low-income housing -- Philippines -- Quezon City; Interior decoration -- Philippines